The Silk Road as a Skilled Practice: taking the two tea roads as cases - CHEN Wei (Археология евразийских степей)
The Silk Road, an ancient network of trade and cultural exchange, has been a subject of significant scholarly interest, particularly in China, Russia, and Mongolia. This paper delves into the skilled practice that underpinned the operation of two major tea roads, emphasizing the continuity of the Silk Road's legacy. It argues for a new approach to the study of cross-cultural exchanges by examining the knowledge systems that supported the movement, adaptation, and exchange of goods and ideas across the Eurasian continent. The author introduces two conceptual tools: "Silk Roadness" to describe the aspects of knowledge reflected in the Silk Road's operation, and "Silk Road+" to denote the transformation that the Silk Road brought to knowledge systems. The paper posits that the Silk Road facilitated the formation, selection, and evolution of knowledge, endowing it with specific functions and creating specialized spaces for its practice. The study focuses on the Eurasian Tea Road ("万里茶道") and the Tea-Horse Road ("茶马古道"), examining the commercial cities, transportation methods, and the specialized skills that evolved along these routes. The author conducted field research in key locations such as Zhangjiakou and Qixian in the Eurasian Tea Road, and in Pu’er and Ya’an along the Tea-Horse Road, gathering information on historical sites, documents, artifacts, and traditional crafts. The paper highlights the distinct roles of Zhangjiakou and Qixian in the Eurasian Tea Road, where Qixian was a hub for Shanxi merchants, and Zhangjiakou served as a critical junction for trade between agricultural and nomadic regions. The author also discusses the Pu'er, Ya’an and Kangding in the Tea-Horse Ancient Road, which was key to the distribution of Yunnan and Sichuan teas to Tibet. The author identifies several key areas of skilled practice along the Silk Road, including commercial practical skills, transportation methods, trade infrastructure, communication and interaction skills, and product packaging and sales strategies. These skills were essential for the successful operation of the trade routes and for adapting to the diverse environments and cultural contexts encountered along the way. The paper concludes by emphasizing the importance of understanding the intricate relationship between the Silk Road and traditional knowledge systems. It calls for continued interdisciplinary research that incorporates the concepts of "Silk Roadness" and "Silk Road+" to build a more comprehensive framework for understanding the Silk Road as a vibrant network of knowledge evolution.